Interdisciplinarity as Academic Accountability: Prospects for Quality Control Across Disciplinary Boundaries. (3rd March 2016) - Huutoniemi, Katri
Abstract : Two major science policy issues are the integration of knowledge across academic disciplines and the accountability of science to society. Instead of adding new or external criteria for research evaluation, I argue, these goals can be pursued by subjecting disciplinary priorities and procedures to broader scrutiny from the rest of academia. From a social epistemological perspective, the paper discusses interdisciplinarity as a mode of epistemic accountability across disciplinary boundaries, which promises to make academia more than the sum of its disciplinary parts. Drawing on discussions of interdisciplinarity and accountability in knowledge production, as well as on empirical findings of the evaluation of research proposals, the paper unpacks the notion of academic accountability into three dimensions—the recipients, contents, and practices of accountability—and illustrates the difference interdisciplinarity makes in each dimension. The analysis shows that interdisciplinarity is not simply a category of research, but involves a social epistemic mechanism of coordination, control, and compromise between disciplinary regimes of knowledge. This framing of interdisciplinarity clarifies its role in the changing governance of science while simultaneously solving central controversies over its meaning in research evaluation.